Personality shapes pair bonding in a wild bird social system. Issue 11 (November 2018) - Firth, Josh; Cole, Ella; Ioannou, Christos; Quinn, John; Aplin, Lucy; Culina, Antica; McMahon, Keith; Sheldon, Ben
Abstract Mated pair bonds are integral to many animal societies, yet how individual variation in behaviour influences their formation remains largely unknown. In a population of wild great tits (Parus major), we show that personality shapes pair bonding: proactive males formed stronger pre-breeding pair bonds by meeting their future partners sooner and increasing their relationship strength at a faster rate. As a result, proactive males sampled fewer potential mates. Thus, personality may have important implications for social relationship dynamics and emergent social structure. How and why individuals of the same species may differ in the way they form pair bonds is not well understood. The authors show that the individual personalities of male great tits (Parus major) regulate how quickly they meet their future partner, and the rate at which they bond with them.